Continental IR Theory: The Best Kept Secret - Jorgensen, Knud Erik (European journal of international relations, 2000)
This article reviews the exotic theoretical landscape of Continental IR Theory (CIRT). While often neglected, or claimed to be uninteresting, or being a franchise business producing copies of theorizing done elsewhere, the article attempts to demonstrate that the discipline of International Relations can benefit significantly from an increased awareness of theorizing on the European continent. Far from being a franchise establishment, CIRT delivers original thought-provoking theorizing and challenging perspectives. An increased awareness of CIRT would probably destroy some of the dearest foundational myths of the discipline but in this case that is the price one must pay if one wants to be internationally minded, not only concerning the subject matter of our activities but also concerning intellectual curiosity.